Photocatalytic Degradation of Rhodamine B Dye and Hydrogen Evolution by Hydrothermally Synthesized NaBH4—Spiked ZnS Nanostructures - Amakali, Theopolina; Živković, Aleksandar; Warwick, Michael E. A.; Jones, Daniel R.; Dunnill, Charles W.; Daniel, Likius S.; Uahengo, Veikko; Mitchell, Claire E.; Dzade, Nelson Y.; de Leeuw, Nora H. (Frontiers in Chemistry, 2022)
Metal sulphides, including zinc sulphide (ZnS) are semiconductor photocatalysts that have been investigated for the photocatalytic degradation of organic pollutants as well as their activity during the hydrogen evolution reaction and water splitting. However, devising ZnS photocatalysts with a high overall quantum efficiency has been a challenge due to the rapid recombination rates of charge carriers. Various strategies, including the control of size and morphology of ZnS nanoparticles have been proposed to overcome these drawbacks. In this work, ZnS samples with different morphologies were prepared from zinc and sulphur powders via a facile hydrothermal method by varying the amount of sodium borohydride used as a reducing agent. The structural properties of the ZnS nanoparticles were analysed by X-ray diffraction (XRD), scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS) techniques. All-electron hybrid density functional theory calculations were employed to elucidate the effect that sulphur and zinc vacancies occurring in the bulk as well as (220) surface have on the overall electronic properties and absorption of ZnS. Considerable differences in the defect level positions were observed between the bulk and surface of ZnS while the adsorption of NaBH4 was found to be highly favourable but without any significant effect on the bang gap of ZnS. The photocatalytic activity of ZnS was evaluated for the degradation of rhodamine B dye under UV irradiation and hydrogen generation from water. The ZnS nanoparticles photo-catalytically degraded Rhodamine B dye effectively, with the sample containing 0.01 mol NaBH4 being the most efficient one. The samples also showed activity for hydrogen evolution, but with less H2 produced compared to when untreated samples of ZnS were used. These findings suggest that ZnS nanoparticles are effective photocatalysts for the degradation of rhodamine B dyes as well as the hydrogen evolution, but rapid recombination of charge carriers remains a factor that needs future optimization.